Pengembangan Quality Control Phantom Berbahan Akrilik dan Aluminium - Aeni, Alfieta Rohmaful; Yudhistira, Danang Noeramarullah (Jurnal Pendidikan dan Ilmu Fisika, 2025)
The high cost of phantoms for Quality Control (QC) in diagnostic imaging remains a challenge for hospitals in non-urban areas. This study developed a simple and affordable phantom using acrylic and aluminum. Ten circular acrylic layers, each 3 mm thick, were stacked and embedded with 15 holes filled with aluminum disks of varying thicknesses (1–15 mm). The phantom was exposed to X-rays at tube voltages of 50 kV, 60 kV, and 70 kV, with 5 ms exposure time and 160 mA current. Gray level analysis using ImageJ showed that 60 kV produced the best image contrast and clear differentiation of aluminum thicknesses. At 50 kV, thicker aluminum (10–15 mm) was hard to distinguish, while at 70 kV, thinner disks (1–5 mm) were less visible. These results indicate that the developed phantom is sensitive to exposure parameter changes and has potential use in educational and basic X-ray imaging system evaluation.